Quality Management System Design for KAP MNL Aligned with SMM 1 Requirements - Hasri, Naura Chairunnisa; Wijayati, Nureni (E-Jurnal Akuntansi, 2026)
This study evaluates the preparedness and efficacy of executing the Quality Management System (SMM 1/ISQM 1) in a Public Accounting Firm by assessing quality hazards, reviewing documentation, and analyzing policy implementation. The findings reveal that although numerous elements of the quality management system are well documented, some areas—especially information systems and communication—fall short of the acceptable standard and necessitate significant enhancement. The documentation assessment indicates a preparedness level of around 71%, while the evaluation of the information system attains just 47%, underscoring a substantial disparity between policy and practice. The report recommends a more complete quality control system design in accordance with SMM 1 to enhance governance, risk assessment procedures, resource proficiency, and monitoring mechanisms. This proposed framework aims to improve the quality of audit engagements and assist the firm in constantly adhering to professional standards.